Insights from a Spatiotemporal Analysis of Top-Performing Bangkok Taxis - Sooksan Panichpapiboon; Kaiden Semapakdi-Chang (My University, 2025)
Taxi is one of the most widely used public transportation systems. It provides a convenient way for people to move around a city. Nonetheless, past studies have shown that traditional street-hail taxis are highly inefficient, as most taxis spend most of their operating time without passengers aboard. However, there are still highly efficient taxis that outperform the others. Learning how these top performers stay ahead of their peers is crucial. This paper analyzes over four million taxi trips in Bangkok and its nearby region to extract meaningful insights from top-performing taxis. Spatial and temporal characteristics of trips made by top performers and ordinary taxis are investigated. These insights are valuable for improving the current taxi service and helpful in planning future mobility services such as autonomous taxis.
Keywords: Transportation and Mobility Innovations; Aviation Industry Analysis and Trends; Transportation Planning and Optimization